Bonjour :)
Réponse en explications étape par étape :
# Exercice n°3 : On considère l'expression " A = (2x + 1)² - (3 - x)(2x + 1) " :
- Questions :
1. Développer et réduire " A " :
A = (2x + 1)² - (3 - x)(2x + 1)
A = (2x)² + (2 * 2x * 1) + (1)² - [(3 * 2x) + (3 * 1) - (x * 2x) - (x * 1)]
A = 4x² + 4x + 1 - (6x + 3 - 2x² - x)
A = 4x² + 4x + 1 - 6x - 3 + 2x² + x
A = 4x² + 2x² + 4x - 6x + x + 1 - 3
A = 6x² - x - 2
2. Calculer " A " pour " x = - 2 " :
A = 6x² - x - 2
A = 6(-2)² - (-2) - 2
A = 6 * 4 + 2 - 2
A = 24
3. Factoriser " A :
A = (2x + 1)² - (3 - x)(2x + 1)
A = (2x + 1)(2x + 1) - (3 - x)(2x + 1)
A = (2x + 1)(2x + 1 - 3 + x)
A = (2x + 1)(3x - 2)
4. Résoudre l'équation " (3x - 2)(2x + 1) = 0 " :
(3x - 2)(2x + 1) = 0
Soit : 3x - 2 = 0 ou 2x + 1 = 0
3x = 2 ou 2x = - 1
x = 2/3 ou x = -1/2
S = { 2/3 ; - 1/2 }
Voilà